Analysis of biomedical images based on automated methods of image registration - João Manuel R. S. Tavares (2014)
This paper gives a review of the methods that we have developed over the last few years to register 2D/3D images and image sequences. Initially, we will introduce a feature-based method, which will be followed up by a summary of the intensity-based methods. Then we will present some applications of our methods using biomedical images with more automated image analysis tasks. The main applications are related to plantar pressure images and SPECT brain images, including both static images and image sequences.